pengaruh pupuk organik cair genetika plus dan jarak tanam yang berbeda terhadap pertumbuhan dan produksi biomas rumput gajah (pennisetum purpureum) - Abdul Karim Madina (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2019)
ABSTRACTAbdul Karim Madina. 2018. The Effect of different Levels of Liquid Organic Fertilizer of Genetika Plus and different Spacing on Growth and Production of Elephantgrass Biomass (Pennisetum purpureum). Supervised by Muhammad Mukhtar as main supervised and Musrifah Nusi as vice supervised.The purpose of this research was to determine the effect of the level of liquid organic fertilizer (LOF) of Genetika Plus and different spacing on the growth and production of elephantgrass biomass (Pennisetum purpureum). This research was conducted in Tamboo Sub-District Tilongkabila, Bone Bolango District, from April to June 2018. The method used in this study is Factorial RAL with two factors. Data were analyzed using analysis of varian. The results showed that under fertilizer treatment and plant spacing had a significantly effect on the growth and production of biomass. The highest plant height was obtained in R3K2 (397 cm) and the lowest in R0K3 (210 cm), the highest tillering production was in R3K3 (7.5) and the lowest was in R0K1 (3.5). Whereas biomass production, the highest in fresh matter weight was obtained in R3K1 (29,076) and the lowest in R0K3 (1,638), the highest leaf blade percentage obtained in R3K1 (38,519) and the lowest in R0K1 (14), the highest dry matter weight was obtained in R3K1 (494) and lowest in R0K3 (27.75). Based on the research, the level of genetics plus liquid organic fertilizer (LOF) and plant spacing has a significantly effected on the growth of elephant grass (Pennisetum purpureum) on plant height, fresh matter production, leaf blade percentage, dry matter production and number of tillers.Key words: Biomass production, elephantgrass, Genetika plus fertilyzer, plant spacing